PERAN ZAKAT DALAM MENGURANGI KESENJANGAN PENDAPATAN DAN KEMISKINAN UMAT ISLAM DI INDONESIA - Rizzky, Dava Muhammad; Naili Fadillah; Nurasyifa Ramahdani (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
Zakat is an important economic tool in Islam, helping communities overcome poverty and promote equitable welfare. In Islamic teachings, zakat is not only a ritual obligation, but also a means of distributing wealth to improve the economic conditions of the community. This study uses a qualitative method through a literature review, analyzing various references such as books, journal articles, verses from the Qur'an, and related hadiths. The results of the study show that zakat can be a powerful tool for reducing poverty by channeling funds to eligible recipients (mustahik). However, there are obstacles such as a lack of public awareness in paying zakat and weak supervision of fund distribution. Therefore, it is necessary to improve the management mechanisms and education about zakat so that its role as an economic solution for the community can be maximized in overcoming poverty in Indonesia.